Some notes on the literature on ancient didactic poetry - Szilágyi, Laura Menta (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The student of ancient didactic poetry has to face a complex web of modern findings and opinions about the genre. This paper attempts to present a few prominent studies from some specific points of view, such as the ways in which they describe the genre (with categorizations and sets of criteria) and in which they delineate ancient views on the genre. The levels of a historical approach and self-awareness in these studies are also examined.